Auditoria de gestión al componente talento humano de la comercializadora Ramírez Galván cía. Ltda. “zerimar”; como base para definir las políticas en el departamento de recursos humanos, en el periodo 2014 - Zhunaula Medina, Doris Alicia (2016)
This paper titled "Auditing the Human Resource component of the Distributor Ramirez Galvan. Cía. Ltda. "Zerimar."; as a basis for defining policy in the Department of Human Resources, in the period 2014 "it has been developed based on a fundamental requirement for the approval of the Engineering in Accounting and Auditing; and be a contribution to the audited company, in order to contribute to the improvement and development of human talent. The objectives of the research were fulfilled assessing the internal control system, determining in the FODA their strengths and weaknesses, using performance indicators to measure the efficiency, economy and quality of human resources of the company; also allowing the identification of findings in the processes through the application of technical audit in compliance with the laws and Audit Reporting Standards concluding with the performance audit report. So too it is annexed a model of policies that could be implemented in the HR department of the audited company. The report issued allowed to know the administrative weaknesses in the management of human resources component of the company, to take corrective measures to reduce the risks in the audited component, so it is recommended to adopt the suggestions raised in the audit, heading for the benefit of it.